Enhanced T helper 1 and 2 cytokine responses at birth associate with lower risk of middle ear infections in infancy. Issue 1 (24th October 2016) - Bergroth, Eija; Roponen, Marjut; Karvonen, Anne M.; Keski‐Nisula, Leea; Remes, Sami; Riedler, Josef; Roduit, Caroline; Dalphin, Jean‐Charles; Kaulek, Vincent; Loss, Georg J.; Lauener, Roger; Hirvonen, Maija‐Riitta; et al.
Abstract: Background: Respiratory tract infections and their symptoms are frequent during early childhood, but their risk factors, including the effect of early immune regulation, are less known. The aim of the study was to analyze whether stimulated cord blood cytokine production is associated with the frequency of respiratory tract infection symptoms or infections during the first year of life. Methods: The study population consisted of children of mothers from farm or non‐farm rural environment from Austria, Finland, Germany, and Switzerland who participated in a prospective birth cohort study (PASTURE: Protection against Allergy—Study in Rural Environments) (N = 550). Cord blood samples were stimulated with the combination of phorbol ester and ionomycin (P/I) for 24 h, and the production of IL‐5, IL‐10, TNF‐α, and IFN‐γ was determined using ELISA. Information about infectious morbidity was collected using weekly diaries. Results: P/I‐stimulated production of IL‐5 (adjusted risk ratio (aRR) for ≤median production, 0.37; 95% confidence interval (CI), 0.25–0.55, aRR for >median production, 0.41; 95% CI, 0.27–0.61 vs. production <detection limit) and IFN‐γ (aRR for ≤median production, 0.62; 95% CI, 0.40–0.95, aRR for >median production, 0.39; 95% CI, 0.25–0.62 vs. production <detection limit) in cord blood were associated with lower number of weeks with reported middle ear infection. There was a tendency toward positive association with P/I‐stimulated TNF‐α production and middle ear infections. Conclusion: Our results suggest that increased Th2‐ and Th1‐associated cytokine responses at birth may provide protection from later middle ear infections.